Certain Varieties of Resolving Sets of A Graph - Badekara Sooryanarayana; Suma A.S.; Chandrakala S.B. (IndoMS, 2021)
Let G=(V,E) be a simple connected graph. For each ordered subset S=s_1,s_2,...,s_k of V and a vertex u in V, we associate a vector Gamma(u/S)=(d(u,s_1),d(u,s_2),...,d(u,s_k)) with respect to S, where d(u,v) denote the distance between u and v in G. A subset S is said to be resolving set of G if Gamma(u/S) not equal to Gamma(v/S) for all u, v in V-S. The purpose of this paper is to introduce various types of r-sets and compute minimum cardinality of each set, in possible cases, particulary for paths, cycles, complete graphs and wheels.